Um Modelo Multiparadigma para Desenvolvimento de Software Paralelo e Distribuído - Barbosa, Jorge Luis Victória; Geyer, Cláudio Fernando Resin (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2000)
This paper presents the Holoparadigm, a new paradigm to parallel and distributed software development. Holoparadigm stimulates the subliminal modeling of the parallelism and its automatic exploitation (implicit parallelism). The proposal is based on multiparadigm and software architecture researches. First of all, the text describes the paradigm's genesis and its semantic (Holosemantic). After that, the distribution and mobility in the work's scope, the architecture style proposed and the principies of a language (Hololanguage) based on the paradigm are discussed. Finally, a plataform of development and execution are described.